INCREASE IN REVENUE OF TOKOPEDIA COMMUNITY YOGYAKARTA FROM THE PERSPECTIVE OF ISLAMIC BUSINESS ETHICS - Arfaizar, Januariansyah (Universitas Islam Indonesia, 2020)
Tokopedia as one of the leading marketplaces in Indonesia has thousands of sellers. One of Tokopedia communities which actively seeks to develop business is Tokopedia Community Yogyakarta. With an increasing number of business players to meet consumer needs, business players face challenges of reaching more buyers and increasing revenue. This study aimed to analyze the increase in revenue of Tokopedia Community Yogyakarta seen from the perspective of Islamic business ethics. This study used a qualitative descriptive method. The results of the research showed that there are several factors that affect the revenue of Tokopedia Community Yogyakarta, namely 1) Products, 2) Promotions, 3) Prices, 4) Services and 5) Other factors including economic conditions and trends, in terms of 5 axioms of Islamic business ethics, namely unity, equilibrium, free will, responsibility and virtue. In fact, the increase in revenue of Tokopedia Communty Yogyakarta has been in line with the principles of Islamic business ethics. However, in terms of prices, there is a violation in the form of a price war, causing both the fall in product prices and disadvantages to other sellers.